The right to be forgotten for cancer survivors in the Italian Law no. 193/2023 (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Following in the footsteps of what is already provided for in several foreign legal systems and also responding to the urging of European institutions, Law no. 193/2023 has introduced in the Italian legal system the right to be forgotten for cancer survivors. According to the new regulation, persons recovered from an oncological pathology have the right not to provide information or be subjected to investigations concerning their previous pathological condition once more than ten years have passed since the end of active treatment of the pathology in the absence of relapses.
Keywords: Cancer survivors; right to be forgotten; discrimination; rehabilitation; patients’ empowerment